1983
DOI: 10.1017/s0141347300008624
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Outcome in the Treatment of Agoraphobia

Abstract: Seventeen female agoraphobic patients were treated in three groups by in vivo exposure over 10 sessions. Dependent measures comprised an assessment using a behavioural hierarchy and an assessment of subjective anxiety. Pre-treatment assessment of the number of problems and fears, interpersonal variables and personality as measured by the E.P.P.S. were also carried out. Correlational evidence was sought of relationships between pre-treatment assessment variables and treatment outcome. It was found that low scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In an intriguing study, Thomas-Peter, Jones, Sinnott, and Scott Fordham (1983) conducted interviews with patients' spouses before treatment on the basis of which they reliably rated how effective the spouses were at managing the patient's illness. These ratings proved to be strongly related to patients' severity of agoraphobia after treatment, with pretreatment severity controlled.…”
Section: Prediction Of Outcome Of Exposure Treatment For Agoraphobiamentioning
confidence: 99%
“…In an intriguing study, Thomas-Peter, Jones, Sinnott, and Scott Fordham (1983) conducted interviews with patients' spouses before treatment on the basis of which they reliably rated how effective the spouses were at managing the patient's illness. These ratings proved to be strongly related to patients' severity of agoraphobia after treatment, with pretreatment severity controlled.…”
Section: Prediction Of Outcome Of Exposure Treatment For Agoraphobiamentioning
confidence: 99%
“…This was Mathews et al's (1977) study of partner-assisted exposure. In the remaining eleven studies, no association was found between the initial quality of couples' relationships and their immediate response to treatment or the severity of PDA symptoms during the follow-up periods of up to sixteen months Barlow et al, 1981;Chambless and Gracely, 1988;Cobb et al, 1984;Craske et al, 1989;Emmelkamp, 1980;Emmelkamp et al, 1992;Himadi et al, 1986;Peter and Hand, 1988;Thomas-Peter et al, 1983). In eight of these studies individually based treatment conditions such as individual exposure therapy were evaluated, and in five studies couples-based treatment conditions such as partner-assisted exposure were evaluated.…”
Section: General Characteristics Of Couples-based Pda Treatment Outcomentioning
confidence: 99%